Comparative analysis of golf clubhead motion at impact - Krasna, S.; Coh, M.; Prebil, I.; Mackala, K. (Facta Universitatis: Series Physical Education and Sport, 2019)
The purpose of the study was to investigate clubhead kinematics during the impact phase of a golf swing. Three highly skilled golfers of a distinguished body type were instructed to perform driver, 6-iron and pitching wedge trials. A high-speed imaging system was used to capture the clubhead motion near the impact. Conventional golf swing parameters were analysed for comparison. Additionally, a circular arc was fitted to the clubhead path, and the moving trihedron was introduced as a reference frame for observing the clubhead rotation. Despite differences in their body type, golfers achieved comparable clubhead speed, while the radius of the fitted circular arc was in a narrow range. The moving trihedron, together with conventional parameters of the golf swing, enabled additional insight to the clubhead motion and clubface orientation. Individual swing characteristics, which result in the clubhead motion prior to impact, could clearly be observed, enabling improvement of the golfer`s swing technique.